2021
DOI: 10.1098/rsob.210242
|View full text |Cite
|
Sign up to set email alerts
|

Darwin's bark spider shares a spidroin repertoire with Caerostris extrusa but achieves extraordinary silk toughness through gene expression

Abstract: Spider silk is a protein-based material whose toughness suggests possible novel applications. A particularly fascinating example of silk toughness is provided by Darwin's bark spider ( Caerostris darwini ) found in Madagascar. This spider produces extraordinarily tough silk, with an average toughness of 350 MJ m −1 and over 50% extensibility, and can build river-bridging webs with a size of 2.8 m 2 . Recent studies have suggested that spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 55 publications
1
41
0
Order By: Relevance
“…Very recent (unpublished) work corroborates our genomic findings and provides even further proteomic details about spidroins found in manually drawn dragline silk and its toughness relative to other, related bark spiders found in Madagascar [ 50 , 51 ]. Specifically, Kono et al report that a set of non-spidroin products they referred to as SpiCE proteins contributes to the composite nature of the fibers and are important to tensile properties.…”
Section: Discussionsupporting
confidence: 83%
“…Very recent (unpublished) work corroborates our genomic findings and provides even further proteomic details about spidroins found in manually drawn dragline silk and its toughness relative to other, related bark spiders found in Madagascar [ 50 , 51 ]. Specifically, Kono et al report that a set of non-spidroin products they referred to as SpiCE proteins contributes to the composite nature of the fibers and are important to tensile properties.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, a number of recent studies, spurred mostly by advances in proteomics and sequencing technologies, paint a more complex picture of dragline silk composition than is provided by a simple MaSp1/MaSp2 dichotomy. 13 20 A subtype termed MaSp3 was identified in several species via proteomics and genomic target capture techniques. 15 , 16 On the other hand, a major study by Babb et al reported at least 8 distinct subtypes of spidroins in the major ampullate silk of Trichonephila clavipes (denoted as MaSp-a to MaSp-h, plus other putative spidroins).…”
Section: Complex Composition Of Spider Dragline Silkmentioning
confidence: 99%
“… 17 The presence of MaSp4 has been linked to the extreme toughness of C. darwini dragline. 17 , 20 , 21 Kono et al used a combination of genomic, transcriptomic, and proteomic approaches to identify spidroin sequences from Araneus ventricosus , 19 which identified the MaSp3 subtype (later assigned to MaSp3A) as the third main component after MaSp1 and MaSp2. The same group likewise identified three main components in the dragline silk from the Nephilinae lineage: MaSp1, MaSp2, and MaSp3B, 18 with the latter being apparently synonymous with the previously identified Sp-74867 spidroin from T. clavipes .…”
Section: Complex Composition Of Spider Dragline Silkmentioning
confidence: 99%
See 2 more Smart Citations